2006
DOI: 10.1007/s00268-005-0472-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Characteristics and Long‐term Outcome in Patients with Distant Metastases from Differentiated Thyroid Cancer

Abstract: We conclude that complete resection of the thyroid gland at diagnosis and high-dose adjuvant radioactive iodine are associated with improved survival in patients with metastatic DTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
76
2
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(87 citation statements)
references
References 31 publications
(62 reference statements)
3
76
2
5
Order By: Relevance
“…With conventional treatments (surgery, radioiodine, hormone suppression), distant metastases (DM) occur in 3%-7% of cases, most often in the lung [1,2].Treatment of DM patients is based on radioiodine and associated with hormone suppression and locoregional therapies [3,4]. Twothirds of DM patients have 131 I uptake on therapeutic 131 I wholebody scan ( 131 I-WBS), and a half of these achieve remission.…”
Section: Introductionmentioning
confidence: 99%
“…With conventional treatments (surgery, radioiodine, hormone suppression), distant metastases (DM) occur in 3%-7% of cases, most often in the lung [1,2].Treatment of DM patients is based on radioiodine and associated with hormone suppression and locoregional therapies [3,4]. Twothirds of DM patients have 131 I uptake on therapeutic 131 I wholebody scan ( 131 I-WBS), and a half of these achieve remission.…”
Section: Introductionmentioning
confidence: 99%
“…Distant metastasis occurs in 4-23% of DTC patients and the lung is the most frequent site of distant metastasis (1-7). The 10-year survival rate after a diagnosis of metastatic DTC ranges from 25% to 70%, and patients with metastatic DTC have markedly varying clinical outcomes from rapid progression and death to complete remission, suggesting a heterogeneity in those patients (2,6,(8)(9)(10)(11)(12)(13)(14). Several retrospective studies have shown that the prognostic factors for the survival of metastatic DTC include age at diagnosis (9,14,15), histology of the tumor (14,16), site of metastasis (14,15), and 131 I avidity (9,15,16).…”
mentioning
confidence: 99%
“…Reported rates of occurrence of distant metastases in DTC range from 6% to 20% with variation between papillary and follicular subtypes (9). Metastatic disease in DTC has a more favorable course than others malignancies with widespread dissemination, with 10-year survival rates of 50% in the majority of series.…”
Section: Discussionmentioning
confidence: 99%